2017
DOI: 10.3349/ymj.2017.58.2.401
|View full text |Cite|
|
Sign up to set email alerts
|

The Level of Serum and Urinary Nephrin in Normal Pregnancy and Pregnancy with Subsequent Preeclampsia

Abstract: PurposeThe aim of this study was to evaluate serum and urinary nephrin levels of normal pregnancy to establish a standard reference value and to compare them with patients who subsequently developed preeclampsia (PE).Materials and MethodsIn this prospective study, 117 healthy singleton pregnancies were enrolled between 6 to 20 weeks of gestation at 2 participating medical centers during October 2010 to March 2012. Urine and serum samples were collected at the time of enrollment, each trimester, and at 4 to 6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This is contrary to urinary nephrin levels, increase along the gestational age and decreases during postpartum. 21,23 The relationship between serum nephrin levels with BP, obtained a weak and signifi cant correlation with systolic with r = 0.36 and p = 0.02 (p <0.05) whereas at diastolic obtained a weak correlation with r = 0.30 but not signifi cant with p = 0.05 (p> 0.05). In this study, isolated systolic hypertension may occur so that a signifi cant correlation exists only in systolic blood pressure.…”
Section: Indones J Obstet Gynecolmentioning
confidence: 98%
“…This is contrary to urinary nephrin levels, increase along the gestational age and decreases during postpartum. 21,23 The relationship between serum nephrin levels with BP, obtained a weak and signifi cant correlation with systolic with r = 0.36 and p = 0.02 (p <0.05) whereas at diastolic obtained a weak correlation with r = 0.30 but not signifi cant with p = 0.05 (p> 0.05). In this study, isolated systolic hypertension may occur so that a signifi cant correlation exists only in systolic blood pressure.…”
Section: Indones J Obstet Gynecolmentioning
confidence: 98%
“…Wang has found that urine nephrin levels correlate with the severity of proteinuria—in other words, the more severe podocyte and slit diaphragm damage the more pronounced the proteinuria [ 19 ]. Jung has noticed that increased urine concentrations of nephrin predate the signs of preeclampsia by an average of nine days [ 20 ]. Additionally, other authors have observed that urinary levels of nephrin are higher in PE patients than both in control group women and patients with gestational hypertension [ 21 ].…”
Section: Urinary Excretion Of Podocytes and Their Proteins Secondamentioning
confidence: 99%
“…) and increased nephrin concentrations in serum and urine (Jung et al . ), but also via thrombotic micro‐angiopathy (Johnson & Nangaku, ). The latter results from increased arterial and venous resistance by inhibition of endothelial NO‐mediated gestational vasodilatation, sympathetic sensitivity (van Drongelen et al .…”
Section: Cardiovascular and Renal Characteristics Of Preeclampsiamentioning
confidence: 99%
“…Both factors are needed for a normal function of the glomerular endothelium (Henao et al 2010). Disrupted endothelial function triggers further impairment of renal function via induction of podocyte dysfunction, with subsequent podocyturia (Craici et al 2014) and increased nephrin concentrations in serum and urine (Jung et al 2017), but also via thrombotic micro-angiopathy (Johnson & Nangaku, 2016). The latter results from increased arterial and venous resistance by inhibition of endothelial NO-mediated gestational vasodilatation, sympathetic sensitivity (van Drongelen et al 2014) and relaxin (Conrad & Davison, 2014).…”
Section: Renal Functionmentioning
confidence: 99%